Fra-2 regulates B cell development by enhancing IRF4 and Foxo1 transcription - Ubieta, Kenia; Garcia, Mireia; Groetsch, Bettina; Uebe, Steffen; Stein, Merle; Ekici, Arif Bülent; Schett, Georg; Mielenz, Dirk; Bozec, Aline; Weber, Georg (Journal of Experimental Medicine, 2017)
The role of AP-1 transcription factors in early B cell development and function is still incompletely characterized. Here we address the role of Fra-2 in B cell differentiation. Deletion of Fra-2 leads to impaired B cell proliferation in the bone marrow. In addition, IL-7-stimulated pro-B cell cultures revealed a reduced differentiation from large pre-B cells to small B cells and immature B cells. Gene profiling and chromatin immunoprecipitation sequencing analyses unraveled a transcriptional reduction of the transcription factors Foxo1, Irf4, Ikaros, and Aiolos in Fra-2-deficient B cells. Moreover, expression of IL7R? and Rag 1/2, downstream targets of Irf4 and Foxo1, were also reduced in the absence of Fra-2. Pro-B cell proliferation and small pre-B cell differentiation were fully rescued by expression of Foxo1 and Irf4 in Fra-2-deficient pro-B cells. Hence, Fra-2 is a key upstream regulator of Foxo1 and Irf4 expression and influences proliferation and differentiation of B cells at multiple stages.
EVALuna2:9366